The effect of a proposed physical therapy program using exercises to rehabilitate certain ankle joint injuries in middle school students - جبر, م.م امير عباس (Sulaimani Journal for Humanities, 2026)
The research aims to design a proposed physical education program using exercises to rehabilitate some ankle joint injuries among middle school students. The research problem is that some students suffer from ankle joint injuries. The research hypothesis is that there is a statistically significant effect of using exercises to rehabilitate some injuries. The researcher used the experimental method with a single-group design, and the research sample was chosen purposively, consisting of (8) students undergoing rehabilitation exercises after medical recovery from Al-Ibtihal Middle School in the Najaf Governorate Education Directorate. This represents (36%) of the original population of (22) injured students registered in sports medicine centers. Appropriate statistical methods were used for the current research. The results of the study showed that the selected rehabilitative physical exercises within the proposed physical education program using exercises to rehabilitate some ankle joint injuries among middle school students have an active role in preventing deformities, and that the rehabilitative exercises have the main role in controlling the body's organs and placing them under the control of the central nervous system.
Keywords: Physical education curriculum; ankle joint injuries; middle school students